Landasan Ontologis dalam Pengembangan Kurikulum Pendidikan Agama Islam pada MI Sultan Fatah Demak - Mujiburrohman, Mujiburrohman; Sholekah, Umma Rohmah (TSAQOFAH, 2025)
Islamic education plays a strategic role in developing human competencies holistically by integrating cognitive, psychomotor, and affective aspects, while emphasizing a balance between spiritual development and scientific knowledge in accordance with the values of the Qur’an and Sunnah. This study aims to explore curriculum integration at MI Sultan Fatah Demak, which combines Islamic and general education through two frameworks: the Kurikulum Merdeka and the pesantren curriculum. Using a qualitative approach, the study analyzes the ontological, epistemological, and axiological dimensions of the curriculum through interviews, observations, and documentation involving students and educators. The findings reveal that the curriculum incorporates both formal and informal components designed to instill spiritual values and religious knowledge systematically. Diverse teaching methods are employed to foster a comprehensive understanding of Islamic principles while preparing students for higher levels of education. This curriculum integration reflects the institution’s commitment to shaping individuals who are faithful, devout, and intellectually competent, while supporting national educational goals within the context of Indonesian culture. The study underscores the importance of a contextual and integrative curriculum design in enhancing the quality of education in madrasahs.